Novel approach for shipborne‐passive bistatic imaging with DVB‐T signals based on MIAA–RID technique. Issue 8 (20th April 2022) - Wang, Yong; Yang, Jiaxing; Yeh, Chunmao; Lu, Xiaofei
Abstract: The shipborne‐passive bistatic inverse synthetic aperture radar system with digital video broadcasting terrestrial (DVB‐T) signals is very important in the fields of radar imaging, but it suffers from the problems of grating lobes caused by the spectral gaps when multiple DVB‐T channels are applied, and the non‐stationary echo signal for the complex motions of the ship. In this paper, a new algorithm based on the Missing Data Iterative Adaptive Approach (MIAA) combined with the Range Instantaneous Doppler (RID) technique is proposed to address these problems. First, the authors establish the imaging geometry and signal model. Based on these models, the range resolution and Doppler frequency are analysed. Then, the bandwidth synthesis in the frequency domain for the DVB‐T signal is derived. Finally, the MIAA method is used to recover the spectral gaps of the range profile for multiple DVB‐T channels, and the azimuth compression is carried out by the RID method after the translational motion compensation. Simulation results show the effectiveness of the algorithm proposed in this paper.